Macroporous Hollow‐Fibrous and Magnetically Recoverable TiO2 Catalysts for Converting Dye Wastewater to Valuable Resources - Xin Liu; Gonggang Liu; Shanshan Chang; Yuanyuan Liao; Jinbo Hu (ChemElectroChem)
The photocatalytic TiO2 has been regarded as a promising catalyst of nonbiodegradable organic pollutants in wastewater. Resolving some issues of agglomeration, recoverability, and poor efficiency, an inorganic TiO2‐based catalyst has been constructed by a template method, which picks out bamboo fibers originating from processing waste. Characterization of the hollow fibrous TiO2/Fe3O4 catalyst confirms the successful loading of Fe3O4 and TiO2, along with a well‐developed macroporous structure and high porosity (67.46%). At a solar intensity of 1 kW/m2, when the amount of TiO2/Fe3O4 is 0.3 g and the amount of H2O2 added is 3 mL, its degradation effect of 88.36% on industrial dye wastewater is optimal. The high magnetic saturation strength (5.78 emu/g) endows TiO2/Fe3O4 with ultra‐high magnetic properties. As expected, after 10 catalytic cycles, the average degradation rate of TiO2/Fe3O4 toward methylene blue (MB) (0.2 L, 10 mg/L) remains above 96.2%, indicating that TiO2/Fe3O4 has ultra‐high recyclability and repeatability. Furthermore, the degradation kinetics analysis shows that TiO2/Fe3O4 exhibits complete degradation of MB within 1 h and the degradation follows quasi‐primary kinetics (k = 06062 min−1, R2 = 0.99747). Free radical burst experiments also indicate that hydroxyl radicals are active species that may play a major role in the solar‐photo‐Fenton system.